King Abdulaziz : a collective bibliography - al muaammar, faisal a. (al-Riya : Maktabat al-Malik Abd al-Aziz al-Ammah, 2002)
Ibn Saud, King of Saudi Arabia, 1880-1953; collective bibliography
Vol. 2 in English
1
Keywords: Ibn Saud, -- King of Saudi Arabia, -- 1880-1953; Ibn Saud, -- King of Saudi Arabia, -- 1880-1953 -- Bibliography; Kings and rulers; Saudi Arabia; Saudi Arabia -- Kings and rulers -- Bibliography; Bibliography